Analisis Keterikatan Emosi dan Hubungan Liniasi para Pemangku Kepentingan dalam Pelestarian Cagar Budaya Keraton di Kota Cirebon - Aziz Ramdani; Muhammad Aziz Ramdani (Bandung Conference Series: Urban & Regional Planning, 2023)
Abstract. Social cohesion is the ability of groups to unite which is formed by cohesiveness through emotional attachment and linear relationships. The current phenomenon of globalization creates a lack of close social relations that can shape individualism which results in accelerating the process of socio-cultural change, especially in cultural acculturation. This concept of social cohesion should be utilized in the continuation of cultural preservation because it sees the importance of preserving culture as an asset and the uniqueness of a region. One of them is the city of Cirebon which still carries out its ancestral culture such as the traditional ceremonies of the Prophet's Birthday and Panjang Jimat and the art of mask dance and has a cultural heritage in the form of the three palace areas. Based on this phenomenon, the purpose of this study is to identify emotional attachments and linear relationships among stakeholders in the preservation of the Cirebon palace's cultural heritage. Researchers used content analysis techniques using a qualitative approach. The results of this study are that there are forms of participation and concern for the regional government and the community for the palace's cultural heritage; The local government cooperates with the palace, namely mask dance training and coaching in the form of educational counseling about the palace; The local government provides APBD funds to the palace every year. It can be concluded that emotional attachment and linear relationships play a role in the preservation of the palace's cultural heritage in the city of Cirebon, both of which can be enhanced by forming a discussion space between actors discussing the direction and plans for preservation as well as providing incentives from the regional service to actors who play an active role in the preservation of the palace's cultural heritage. Abstrak. Kohesi sosial adalah kemampuan kelompok untuk bersatu yang dibentuk oleh kekompakan melalui keterikatan emosi dan hubungan liniasi. Fenomena globalisasi saat ini menimbulkan kurangnya keeratan hubungan sosial yang membentuk sifat individualisme yang mengakibatkan perubahan sosial budaya khususnya dalam akulturasi budaya. Konsep kohesi sosial ini seharusnya dapat dimanfaatkan dalam keberlangsungan pelestarian budaya karena melihat pentingnya melestarikan budaya sebagai asset dan keunikan suatu daerah. Kota cirebon yang masih menjalankan budaya leluhur seperti upacara adat Maulid Nabi dan Panjang Jimat serta kesenian Tari topeng serta memiliki cagar budaya berupa kawasan ketiga keraton. Berdasarkan fenomena tersebut, maka tujuan dalam penelitian ini yaitu mengidentifikasi keterikatan emosi dan hubungan liniasi para pemangku kepentingan pelestarian cagar budaya keraton Cirebon. Peneliti menggunakan metode teknik analisis isi dengan menggunakan pendekatan kualitatif. Hasil dari penelitian ini adalah ada bentuk partisipasi dan kepedulian Pemda serta masyarakat terhadap cagar budaya keraton; Pemda melakukan Kerjasama dengan keraton yaitu pelatihan tari topeng serta pembinaan berupa penyuluhan pelajaran mengenai keraton;Pemda memberikan dana APBD kepada keraton tiap tahunnya. Dapat disimpulkan bahwa keterikatan emosi dan hubungan liniasi berperan terhadap pelestarian cagar budaya keraton di Kota Cirebon, keduanya dapat ditingkatkan dengan membentuk ruang diskusi antar para aktor membahas mengenai arah dan rencana pelestarian serta pemberian insentif dari dinas daerah kepada aktor yang berperan aktif dalam pelestarian cagar budaya keraton.